IMPLEMENTASI SISTEM PENGISIAN DAYA DAN PENYIMPANAN ENERGI SURYA DENGAN TEKNOLOGI BATERAI LITHIUM-ION - Sefnath J. Wattimena; Luwis H. Laisina; Conny E. O. Pelamonia (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Solar energy, as a renewable energy source, has gained popularity due to its clean and sustainable electricity generation. Lithium-ion battery technology has enabled efficient storage of solar energy. This study aims to evaluate the efficiency of solar energy charging and storage systems using lithium-ion technology. The research methodology combines quantitative and qualitative approaches. Quantitative data were collected from field tests and surveys, while qualitative data were obtained from interviews and case studies. The results indicate that solar power systems with lithium-ion batteries can reliably meet electricity needs. Additionally, the decreasing costs of solar panels and lithium-ion batteries make this solution more affordable and significantly reduce reliance on fossil fuels and greenhouse gas emissions. The study concludes that the combination of solar power and lithium-ion batteries provides a cleaner, more sustainable, and efficient energy alternative.